2019
DOI: 10.1177/1099800419890424
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Anxiety, Inflammation, and Telomere Length in Postpartum Women: A Pilot Study

Abstract: Background: The postpartum period can be a vulnerable time during which many women are prone to mood disturbances. Since telomere length (TL) is known to be associated with dysphoric moods, inflammation, and stress in many populations, this study’s objective was to assess the relationships among TL, dysphoric moods, stress, and inflammation during the postpartum period. Method: This cross-sectional pilot study is a secondary analysis of data collected in a larger parent study of anti-thyroid peroxidase (TPO) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Four studies were cross-sectional articles, four studies were case-control articles and three were longitudinal studies (Table 3). Seven studies (9103 patients) observed a negative association between TL and anxiety [21,26,31,34,35,68,69], while only one study observed a positive association (132 patients) [42]. One study (1164 patients) reported conflicting results [11] while the two last studies (838 patients) did not observe any association [70,71].…”
Section: Tl and Anxiety Disordersmentioning
confidence: 96%
See 2 more Smart Citations
“…Four studies were cross-sectional articles, four studies were case-control articles and three were longitudinal studies (Table 3). Seven studies (9103 patients) observed a negative association between TL and anxiety [21,26,31,34,35,68,69], while only one study observed a positive association (132 patients) [42]. One study (1164 patients) reported conflicting results [11] while the two last studies (838 patients) did not observe any association [70,71].…”
Section: Tl and Anxiety Disordersmentioning
confidence: 96%
“…A total of 11 studies (11,237 patients) assessed the relationship between anxiety and TL [11,21,26,31,34,35,42,[68][69][70][71]. Four studies were cross-sectional articles, four studies were case-control articles and three were longitudinal studies (Table 3).…”
Section: Tl and Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines such as CRP and IL-6 were also found to be predictive of cognitive symptoms of depression in a 12-year follow-up study . The increased levels of peripheral proinflammatory mediators such as CRP, TNF-α, and IL-6 negatively impact the psychopathology of depression, anxiety, and leukocyte TL (LTL). Thus, inflammation plays a critical role in the manifestation of depression and its long-term sequelae (Table ).…”
Section: Telomere Attrition and Depressionmentioning
confidence: 99%
“…Our previous study confirmed that plasma chromogranin A levels were increased in health workers with anxiety or depression, and chromogranin A is regarded as an indicator of sympathetic tone and adrenomedullary system activity, indicated sympathetic overactivation in patients with anxiety or depression. 22 Fan et al 23 found increased levels of TNFα and IL-6 in patients with depression, while Groer et al 24 demonstrated a significant increase in IL-6 levels in patients with postpartum anxiety.…”
Section: Ta B L E 1 Differences In Clinical and Laboratory Data Betwe...mentioning
confidence: 99%